Efficacy of Mudan Granule (Combined With Methylcobalamin) on Type 2 Diabetic Peripheral Neuropathy: Study Protocol for a Double-Blind, Randomized, Placebo-Controlled, Parallel-Arm, Multi-Center Trial - Zhang, Yuehong; Jin, De; Duan, Yingying; Hao, Rui; Chen, Keyu; Yu, Tongyue; Lian, Fengmei; Tong, Xiaolin (Frontiers in Pharmacology, 2021)
Abstract Background: Diabetic peripheral neuropathy (DPN) characterized by nerve damage is a common and disabling chronic microvascular complication in patients with type 2 diabetic mellitus (T2DM), affecting at least half of patients diagnosed with T2DM. Unfortunately, the current treatment for DPN is not ideal. Traditional Chinese medicine (TCM), with a unique theoretical system, has made outstanding contributions in the treatment of T2DM and related complications. Mudan granule, a Chinese patent medicine, has been previously validated that could ameliorate the symptoms, promote nerve tissue repair, increase nerve conduction velocity (NCV) in patients with DPN. However, the previous studies are of variable quality, which limits the clinical application of Mudan granule. Therefore, we designed a double-blind, randomized, placebo-controlled, parallel-arm, multi-center trial to estimate the safety and efficacy of Mudan granule in conjunction with methylcobalamin in individuals suffering from type 2 diabetic peripheral neuropathy. Methods: This work is conducted as a 14-center, double-blind, randomized, placebo-controlled, parallel-arm trial. In all, 402 subjects (aged 30–70 years) will be recruited and randomized in a 1:1 ratio to an intervention group (n=201; Mudan granule + methylcobalamin) and a control group (n=201; placebo + methylcobalamin). Treatment is administered in 24-week cycles without any treatment interruption between cycles. Michigan Diabetic Neuropathy Score (MDNS) as the primary outcome will be evaluated at baseline, 12 weeks during the intervention period, and after 24 weeks of the intervention. Adverse events and safety assessments will be also documented. The analysis of all data will be carried out based on a predefined statistical analysis plan. Discussion: The outcomes from this study will offer important evidence regarding the safety and efficacy that Mudan granule can be used as an alternative and complementary therapeutic intervention in patients with type 2 diabetic peripheral neuropathy. Clinical trial registration: Registered at https://clinicaltrials.gov/. Trial registration number: NCT04711980. Registered January 2021.